Chemokines encoded by herpesviruses. Issue 5 (1st November 2017) - Pontejo, Sergio M; Murphy, Philip M
Abstract : Review on viral chemokine homologues identified in Herpesviridae family, their implications in viral pathogenesis and leukocyte migration, and their potential clinical applications. Abstract: Viruses use diverse strategies to elude the immune system, including copying and repurposing host cytokine and cytokine receptor genes. For herpesviruses, the chemokine system of chemotactic cytokines and receptors is a common source of copied genes. Here, we review the current state of knowledge about herpesvirus-encoded chemokines and discuss their possible roles in viral pathogenesis, as well as their clinical potential as novel anti-inflammatory agents or targets for new antiviral strategies.